Pharmacokinetics of single- and multiple-dose flumatinib in patients with chronic phase chronic myeloid leukemia - Jiang, Bo; Qi, Junyuan; Sun, Mingyuan; Zheng, Weiwei; Wei, Yongyue; Wang, Jianxiang; Zhang, Fengkui (Frontiers in Oncology, 2023)
Flumatinib is a novel, oral breakpoint cluster region-abelson (BCR-ABL) tyrosine kinase inhibitor that has demonstrated manageable safety and promising efficacy in patients with newly diagnosed chronic phase (CP) chronic myeloid leukemia (CML). This study evaluated the pharmacokinetic (PK) profiles of flumatinib mesylate tablets at a dose of 400 mg and 600 mg in patients with CML-CP. The study was registered at chictr.org Identifier (ChiCTR2100044700). In this open-label, pharmacokinetic study, eligible patients were administered a single-dose of flumatinib 400 mg or 600 mg on day 1, followed by 2-day washout and 8 consecutive days of once-daily administration. Serial plasma samples were assayed for flumatinib and its metabolites (N-demethylate metabolite M1 and amide-bond hydrolytic metabolite M3). Twenty-nine patients were assigned to flumatinib 400 mg (n=14) or 600 mg (n=15). Serum concentrations of flumatinib reached maximum measured plasma concentration (Cmax) at a median time of 2 hours after each single dose, and then eliminated slowly with a mean apparent terminal disposition half-life (t1/2) from 16.0 to 16.9 hours. Following single- and multiple-dose administration, flumatinib exposure (Cmax, area under the concentration-time curve from 0 to t hours (AUC0-t), area under the concentration-time curve from 0 hours to infinity (AUC0-∞)) increased in an approximately dose-proportional manner. There was approximately 4.1- and 3.4- fold drug accumulation at steady-state after multiple-dose administration at 400 mg and 600 mg, respectively. The drug-related AEs associated with both treatments were primarily low-grade and tolerable events. Analysis of PK parameters indicated that flumatinib exposure increased in an approximately dose-proportional manner. Further research needs to be conducted in a large sample-size study.